Building blocks for persistent memory: How to get the most out of your new memory? - Van Renen, Alexander; Vogel, Lukas; Leis, Viktor; Neumann, Thomas; Kemper, Alfons (Vldb Journal, 2020)
I/O latency and throughput are two of the major performance bottlenecks for disk-based database systems. Persistent memory (PMem) technologies, like Intel’s Optane DC persistent memory modules, promise to bridge the gap between NAND-based flash (SSD) and DRAM, and thus eliminate the I/O bottleneck. In this paper, we provide the first comprehensive performance evaluation of PMem on real hardware in terms of bandwidth and latency. Based on the results, we develop guidelines for efficient PMem usage and four optimized low-level building blocks for PMem applications: log writing, block flushing, in-place updates, and coroutines for write latency hiding.
CRIS-Team Scopus Importer:2021-04-12
Keywords: Databases; Persistent memory; Systems